The protective role of propolis in cyclophosphamide-induced cardiotoxicity in rats - Kaya, Emre; Yilmaz, Seval; Colakoglu, Neriman (Ankara Univ Press, 2019)
In the study, the effects of propolis on the cardiotoxicity of cyclophosphamide (CP), a broadly clinically used alkylating chemotherapeutic drug proven to be effective in the treatment of cancer and non-malignant diseases, were investigated. Rats were divided into four groups as follows; control group, propolis treated group (200 mg/kg/day gavage for 7 days), CP treated group (150 mg/kg single dose i.p.), and CP+ propolis treated group. The application of propolis was started 2 days before CP treatment and continued 7 days. Heart tissue was taken for biochemical and histopathological examinations. Malondialdehyde (MDA), reduced glutathione (GSH) levels, catalase (CAT), glutathione peroxidase (GSH-Px), glutathione-S-transferase (GST), superoxide dismutase (SOD) activities were determined in heart tissue. For histopathological examination, heart tissue samples were prepared by appropriate methods and examined after stained with Masson's trichrome and hematoxylin-eosin technique. A significant increase in MDA, GSH levels and CAT activity were detected in the CP-treated group, whereas GSH-Px, GST and SOD activities were decreased (p<0.05). MDA, GSH levels and antioxidant enzyme activities in the CP+ propolis treated group was observed that reached its normal level. Propolis treated group and CP+ propolis treated group observed no statistically significant change. In the histopathological examinations, the sections of the heart tissue in the control group were observed in normal structure. Heart tissue showed a similar structure with the control group in the propolis treated group. Hemorrhage and vascular congestion in some areas of the cardiac muscle fibers were observed in the CP-treated group. CP+ propolis administration caused locally vascular congestion. It is estimated that oxidative stress may play a role in the pathogenesis of CP-induced cardiotoxicity and propolis may reduce the side effects related to CP.
Ratlarda siklofosfamidin sebep olduğu kardiyotoksisitede propolisin koruyucu rolü
Keywords: Antioxidant; cyclophosphamide; heart; malondialdehyde; propolis